Hubungan Kepatuhan Penerapan Pediatric Early Warning Score (PEWS) dengan Kepatuhan Menjaga Keselamatan Pasien di RSUI Harapan Anda Kota Tegal - Devi Apriliyani; Nopi Nur Khasanah; Kurnia Wijayanti (Lembaga Pengembangan Kinerja Dosen, 2025)
In order for hospitals to detect and intervene early, pediatric patient care must be of high quality. When making clinical decisions, assessing the risk of clinical deterioration, and providing appropriate emergency and critical care, the Pediatric Early Warning Score (PEWS) can be an excellent tool for nurses. This study aims to determine how Harapan Anda Hospital in Tegal City applies patient safety compliance and adherence to PEWS implementation. A cross-sectional approach was used in this quantitative study. A complete sampling approach was used to generate a sample size of 88 nurses from various healthcare facilities, including pediatric inpatient wards, PICU, NICU, and the emergency department. Patient safety surveys and PEWS compliance surveys were used to collect data. Spearman's test was used to analyze the data. The results showed that the majority of individuals (45 out of 63) were categorized as compliant in the implementation of the Pediatric Early Warning Score (PEWS). Meanwhile, the majority of nurses, 41 out of 106, or 46.6%, were compliant in their efforts to ensure patient safety. There was a significant relationship between the compliance of PEWS implementation and patient safety at RSU Islam Harapan Anda Tegal City with a p-value of 0.000. The results of this study are expected to be applied by healthcare workers to implement PEWS according to procedure, in order to ensure pediatric patient safety quickly and accurately.